Enhancing the Quality of Learning Based on Character Education at Nurul Istiqlal Islamic Boarding School in Klaten - Mudijono; Sukari (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the improvement of learning quality based on character education at Nurul Istiqlal Islamic Boarding School, Klaten. The research employed a qualitative descriptive approach with an educational evaluation perspective. The study was conducted to examine how character education is implemented in the learning process and to assess its contribution to improving learning quality among students (santri). The research methodology involved observations, in-depth interviews, and documentation analysis. The research sample consisted of 30 santri, selected purposively to represent variations in learning achievement and participation. Data were analyzed using interactive qualitative analysis techniques, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of character-based learning showed a positive impact on learning quality. The effectiveness level of character-based learning implementation reached 82.3%, categorized as good. Specifically, the improvement in students’ learning discipline reached 84.6%, learning motivation 80.9%, moral behavior development 83.1%, and student participation in learning activities 80.7%. These results demonstrate that character education plays a significant role in enhancing learning quality in Islamic boarding schools.This study concludes that character education-based learning is effective in improving both academic and moral aspects of students. Therefore, strengthening character education integration in the learning process is recommended as a strategic effort to enhance the quality of education in Islamic boarding schools.